Determinants of preference of source of injectable contraceptives among rural women in Uganda: a case study of Depo-Provera. - Nakayiza, Olivia; Wamala, Robert; Kwagala, Betty (African Journal of Reproductive Health, 2014)
Understanding preference of source of contraceptive commodities is essential in enhancing the delivery of family planning services. This paper identifies the determinants of preferred source of Depo-Provera among rural women in Uganda. The analysis is based on data sourced from a Save the Children and Family Health International study involving 642 women who were introduced to the contraceptive three years prior to the evaluation. Data were analyzed at univariate, bivariate and multivariate levels. Private sources were the most preferred of Depo-Provera as compared to public sources. Preference for private sources was more likely among older women (p < 0.05), those who had never experienced stock-outs of Depo-Provera (p < 0.01), and those who had obtained their last injectable from private sources (p < 0.01). These findings support the strategy of community-based distribution of contraceptives in enhancing access and utilization of family planning services in Uganda.